Balloon valvuloplasty for valvar pulmonary stenosis: A 34-year experience at a large tertiary-level hospital, Southern Africa - Raphulu, Phophi; Lebea, Mamaila Martha; Cilliers, Antoinette (SA Heart Journal, 2024)
Background: Congenital pulmonary valve stenosis (PS) is one of the most common congenital cardiac defects, accounting for 8 – 12% of all congenital cardiac defects. Percutaneous balloon pulmonary valvuloplasty (PBPV) has been the preferred treatment since its introduction in 1982. Aim: To evaluate the efficacy and safety of PBPV over the last 3 decades at a single institution. Method: A retrospective, descriptive analysis was conducted at a tertiary-level hospital in Southern Africa to evaluate patients who underwent PBPV between 1985 and 2019. Results: During the study period, 68 patients underwent balloon valvuloplasty for moderate to severe pulmonary stenosis. Patients were selected using echocardiographic criteria. The mean pulmonary valve annulus measured on angiography was 11.2mm (SD 3.9) with a mean balloon size of 13.1mm (SD 4.4). The balloon size to pulmonary valve annulus ratio was 1.169:1. The median peak instantaneous gradient (PIG) before balloon valvuloplasty was 79mmHg (IQR 64 - 102mmHg) which decreased to 33mmHg (IQR 23 - 40mmHg) after balloon valvuloplasty (p<0.001). There was an 88% success rate. Complications occurred in 8/68 (11.7%) patients, with 1 procedural death reported. Conclusion: Our study shows that PBPV is a safe and effective treatment of moderate and severe PS with a good outcome. Complications are rare if the procedure is well planned and managed promptly if they arise.